2009
DOI: 10.1021/ja809195s
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Photodissociation Dynamics of a Hexaarylbiimidazole Derivative with Pyrenyl Groups: Dispersive Reaction from Femtosecond to 10 ns Time Regions

Abstract: The photodissociation dynamics of a hexaarylbiimidazole (HABI) derivative with two pyrenyl groups was investigated by time-resolved transient absorption spectroscopy and fluorescence measurements. Transient absorption spectroscopy revealed that photodissociation took place in the wide time region of <100 fs to 10 ns. On the other hand, fluorescence time profiles showed the dynamic red shift in the time region <100 ps. The apparent dispersive photodissociation process was attributed to the increase in the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(43 citation statements)
references
References 44 publications
4
39
0
Order By: Relevance
“…Despite the great progress in increasing the device PCE from initial 3.8% 4 to the most recent 23.3% 5 in just one decade, the commercialization of this technology remains hindered by the stability issues of materials. It has been reported that the perovskites rapidly degrade under increased temperature 6 , oxygen 7 , moisture 8 , and UV light illumination 9 , often due to the structure instability caused by electromigrations 10 , ion migration, 11 and interfacial relationships 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite the great progress in increasing the device PCE from initial 3.8% 4 to the most recent 23.3% 5 in just one decade, the commercialization of this technology remains hindered by the stability issues of materials. It has been reported that the perovskites rapidly degrade under increased temperature 6 , oxygen 7 , moisture 8 , and UV light illumination 9 , often due to the structure instability caused by electromigrations 10 , ion migration, 11 and interfacial relationships 12 .…”
Section: Introductionmentioning
confidence: 99%
“…While PDPP4T is known as a semiconducting D–A polymer with high thin film charge mobility, the selection of the HABI compound is based on the following considerations: i) HABI can be fragmented into a pair of 2,4,5‐triphenylimidazolyl radicals (TPIRs) upon interactions with external stimuli such as light irradiation, and such radical pair can thermally recombine to regenerate HABI . In fact, Abe and others have intensively investigated the photochromic behaviors of HABI derivatives with widely tunable absorptions and fast responsiveness; ii) TPIRs like other organic radicals are expected to have high singly occupied molecular orbital (SOMO) levels, and as a result charge doping or formation of charge‐transfer complexes with the semiconducting polymer or interactions with charge defects at the gate dielectric‐semiconductor interface and within the semiconducting thin film are likely to occur according to previous studies . Therefore, the semiconducting performances of the transistors can be tuned accompanying the formation and recombination of the radical pairs of HABI.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the semiconducting performances of the transistors can be tuned accompanying the formation and recombination of the radical pairs of HABI. However, TPIRs are thermodynamically unstable and they rapidly recombine to form the respective HABIs 18d. Thus, we have to design and synthesize new HABI compounds to enhance the stability of the respective TPIRs.…”
Section: Methodsmentioning
confidence: 99%
“…Diffusion of TPIR is thus annihilated [102]. The back-reaction is considerably accelerated and takes place in 180 ms. Other compounds, structured identically, have been the subject of several studies to modulate photochromic properties [103] or to understand the photodissociation mechanism [104].…”
Section: Fast Photochromic Systems: Reverting Back Spontaneously To Tmentioning
confidence: 99%